(untitled) (Applied Biological Research, 2012)
Arsenic (As) is the most hazardous toxic metalloid found in natural ecological units and is widely distributed in various parts of the world. Nearly about 50 million people suffer from its toxicity in Indo-Gangetic alluvium particularly in West Bengal. Present studywas aimed to evaluate As accumulation in pumpkin (Cucurbita moschata), varietal tolerance, As intake and dietary risk in Nadia (West Bengal) during summer 2008-09 and 2009-10 where contaminated ground water is frequently used for irrigation. The experiment was laid out in a randomized block design using 5 pumpkin cultivars each replicated 4times. As uptake and its translocation to the edible parts varied in the pumpkin cultivars grown. Provisional tolerable weekly intake (PTWI) of inorganic As was 15 µg body weight-1. The locally grown cultivar showed maximum As accumulation but lower yield, whereas high yielding cultivars ‘Kali Kumro’ and ‘Ambili’ had less As load in fruits. As accumulation in different parts of pumpkin remained in an order of root > stem > leaf > fruit across the cultivars.